A panel data study on the effects of agricultural land conversion to income inequality - Domasian, Jessica (School of Economics, University of the Philippines Diliman, 2019)
As a developing country, policymakers of the Philippines should be interested in developing strategies in order to improve income distribution and reduce poverty. Understanding and explaining factors that affect income inequality is potentially useful for policymakers in creating and implementing policies addressing this issue. This paper thus investigates whether the changes in land use due to conversion of agricultural lands to commercial, industrial, institutional, recreational, residential, tourism or mixed use has an effect on income inequality across regions. The researchers make use of the Family Income Expenditure Survey (FIES) from years 1994 to 2015 with a three_year gap to compute for the Gini coefficient (a measurement of the degree of income inequality). Through the use of Pooled OLS, Fixed Effect and Random Effect Estimator, the hypothesis is tested using a series of socioeconomic factors that affect income inequality as explanatory variables. The results show that there is a robustly negative association between agricultural land conversion to commercial land use and income inequality, suggesting that land conversion for commercial purposes provides better income_generating and_or employment opportunities for the surrounding localities.